Understanding Implicit Bias: Putting the Criticism into Perspective. (5th January 2020) - Brownstein, Michael; Madva, Alex; Gawronski, Bertram
Abstract: What is the status of research on implicit bias? In light of meta‐analyses revealing ostensibly low average correlations between implicit measures and behavior, as well as various other psychometric concerns, criticism has become ubiquitous. We argue that while there are significant challenges and ample room for improvement, research on the causes, psychological properties, and behavioral effects of implicit bias continues to deserve a role in the sciences of the mind as well as in efforts to understand, and ultimately combat, discrimination and inequality.